2008
DOI: 10.1038/cdd.2008.77
|View full text |Cite
|
Sign up to set email alerts
|

Calphostin C-induced apoptosis is mediated by a tissue transglutaminase-dependent mechanism involving the DLK/JNK signaling pathway

Abstract: A role for tissue transglutaminase (TG2) and its substrate dual leucine zipper-bearing kinase (DLK), an upstream component of the c-Jun N-terminal kinase (JNK) signaling pathway, has been previously suggested in the apoptotic response induced by calphostin C. In the current study, we directly tested this hypothesis by examining via pharmacological and RNA-interference approaches whether inhibition of expression or activity of TG2, DLK and JNK in mouse NIH 3T3 fibroblasts and human MDA-MB-231 breast cancer epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
2
27
0
4
Order By: Relevance
“…This mechanism of TG-2 on JNK has been reported in the context of cell death signaling. 37,38 Consistent with this observation, silencing of TG-2 has been associated with reduced pJNK in malignancies. 37,39,40 Moreover, it has been reported that JNK can localize to paxillin-containing focal adhesions in corneal epithelial cells.…”
Section: Hypothesissupporting
confidence: 67%
“…This mechanism of TG-2 on JNK has been reported in the context of cell death signaling. 37,38 Consistent with this observation, silencing of TG-2 has been associated with reduced pJNK in malignancies. 37,39,40 Moreover, it has been reported that JNK can localize to paxillin-containing focal adhesions in corneal epithelial cells.…”
Section: Hypothesissupporting
confidence: 67%
“…TG2 overexpression and activation have been linked to induction of apoptosis (3,11,12,33). Recently, we reported a possible role of TG2 in the PDT-induced apoptotic death of cancer cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…TG2 promotes apoptosis of cardiomyocytes by reducing phospholipase C␦1 and active PKC levels during oxidative stress (10). TG2 also mediates calphostin C-induced apoptosis via a mechanism involving activation of the c-Jun N-terminal kinase and translocation of Bax to the mitochondria in NIH3T3 fibroblasts and breast cancer cells (11). These events ultimately stimulate a caspase-dependent pathway.…”
mentioning
confidence: 99%
“…To examine the role of TG2 in pulmonary fibroblast function, TG2 was knocked down using an SH-RNA lentivirus vector containing GFP, and cells were sorted for GFP expression (42). This strategy resulted in very efficient 85% knockdown of TG2 protein levels ( Figure 7A and data not shown).…”
Section: Knockdown Of Tg2 In Primary Human Lung Fibroblasts Leads To mentioning
confidence: 99%
“…Sh-RNA lentiviral vectors targeting TG2 and a scrambled Sh-RNA were used as described (42), and cells were sorted for green fluorescent protein (GFP) expression using a FACSAria machine (BD Biosciences). For collagen gel contraction assays, transduced cells were seeded in gels of rat-tail collagen, (Roche, Basel, Switzerland), floated in media, and weighed after 48 hours (43).…”
Section: Tg2 Knockdown and Overexpressionmentioning
confidence: 99%